PRIORITY VECTORS OF PROFESSIONAL TRAINING OF MODERN SPECIALISTS IN FINE ART (Bulletin of Taras Shevchenko National University of Kyiv. Social Work, 2020)
The priority vectors of professional training of contemporary specialists of fine arts in the educational environment of higher education institutions are considered in the article. It is noted that in the modern labor market employers are not interested in a set of theoretical knowledge, but professional competence, which is the basis for successful professional self-realization of modern specialists, including specialists in fine arts, which helps them to solve successfully the problems in social and pedagogical activity as a part of the professional field.The essence of competence approach in professional training of specialists as an important methodology of reform and modernization changes is investigated and revealed. It is noted that the process of professional training of specialists in fine arts requires certain changes in a number of segments of educational theory and practice: in values, in the goal, in the results of the educational process, in its content, forms, methods, means of education in interaction with the external environment. Attention is paid to the fact that the professional training of the specialist of fine arts will be productive, if it will be formed as a coherent system and all components of which will be maximally integrated into a single whole and focused on the implementation of basic professionally significant goals, practical activities of modern specialists in social and practical education.The importance of successful social space of an educational institution in the process of qualitative training of specialists of fine arts is substantiated, the signs of modern social space are determined: intellectual work of students, coordinated interaction, creative cooperation, correctness of interpersonal relations, mutual respect, psychological comfort, freedom of participation.
Keywords: competence, educational space, modern specialist, integrity, professional training.